2017
DOI: 10.1186/s13071-017-2541-6
|View full text |Cite
|
Sign up to set email alerts
|

The Asian fish tapeworm Schyzocotyle acheilognathi is widespread in baitfish retail stores in Michigan, USA

Abstract: BackgroundThe Asian fish tapeworm Schyzocotyle acheilognathi (Yamaguti, 1934) is an important fish pathogen because of its wide range of intermediate and definitive hosts and its pathological consequences. This study was designed to determine if baitfish are a likely vector contributing to the expansion of the invasive Asian fish tapeworm.ResultsWe collected live baitfish for examination from 78 retail stores in Michigan between September 2015 and June 2016. A total of 5400 baitfish (90 lots, 60 fish/lot) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…Ecological impacts of alien invasive shes include the displacement and extinction of native species (Mills et al, 2004;Haubrock et al, 2018), modi cation of trophic interactions (Martin et al, 2010;Haubrock et al, 2019) and disruption of ecosystem functioning (Capps & Flecker, 2013). Fish invaders can also transmit novel pathogens (Gozlan et al, 2005;Waicheim et al, 2014;Ercan et al, 2019;Boonthai et al, 2017) as well as cause genetic pollution via the hybridization with native species (Oliveira et al 2006, Gunnell et al 2007). Introductions of alien sh species into previously shless insular systems can additionally exacerbate impacts due to resident species naiveté (Knapp et al, 2001, Lecomte et al, 2013Cuthbert et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Ecological impacts of alien invasive shes include the displacement and extinction of native species (Mills et al, 2004;Haubrock et al, 2018), modi cation of trophic interactions (Martin et al, 2010;Haubrock et al, 2019) and disruption of ecosystem functioning (Capps & Flecker, 2013). Fish invaders can also transmit novel pathogens (Gozlan et al, 2005;Waicheim et al, 2014;Ercan et al, 2019;Boonthai et al, 2017) as well as cause genetic pollution via the hybridization with native species (Oliveira et al 2006, Gunnell et al 2007). Introductions of alien sh species into previously shless insular systems can additionally exacerbate impacts due to resident species naiveté (Knapp et al, 2001, Lecomte et al, 2013Cuthbert et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Anglers and aquarists potentially play a role in these processes, as the transport and exchange of live individuals between and among these hobbyist groups establishes novel pathways and increases the frequency of translocation of propagules (Figure 6). Another pressing conservation issue related to non‐native fish in the context of anglers and aquarists is the translocation of diseases and parasites: recent research has shown that the activities of anglers can transmit diseases by introducing disease‐carrying baitfish (Boonthai et al, 2017, 2018). Thus, anglers and aquarists acting in concert may potentially pose a greater threat to the conservation of native freshwater ecosystems than the individual actions of these hobbyist groups alone.…”
Section: Resultsmentioning
confidence: 99%
“…Schyzocotyle acheilognathi was morphologically identi ed in 40.0% of the sh, representing a signi cant threat to traditional sheries (Oros et al 2015). In a more recent study, the live bait sh trade was emphasised as an important transmission vector for S. acheilognathi, to infect native sh communities (Boonthai et al 2017). The use of live bait in the USA can compromise aquaculture facilities (Kilian et al 2012) and AFT can spread to novel areas via bait-bucket introductions (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…minnows) with direct release of infected sh. Samples collected in a study from 78 retail stores in Michigan showed that bait sh had a prevalence of tapeworms as high as 58.0% (Boonthai et al 2017).…”
Section: Introductionmentioning
confidence: 99%